Collective action in plant genetic resources management: gendered rules of reputation, trust and reciprocity in Kerala, India - Padmanabhan, Martina Aruna (International Food Policy Research Institute, 2006)
Collective action aims at the joint management of common pool resources. Agrobiodiversity at the community level is conceptualized as a collective resource requiring the management of varieties, species and their interrelations within a farming-system. In the rice dominated agriculture in the uplands of Kerala, India, few community groups continue maintaining and thus conserving their high diversity in landraces. Faced with the challenges of devastating prices for rice, their traditional system of collective action to exchange seed material and knowledge is endangered. A new institutional mechanism to manage biodiversity is the People’s Biodiversity Register, a mandatory documentation procedure to enable cost and benefit sharing under the Convention on Biological Diversity. The comparative analysis of these contrasting cases of an indigenous and an administered effort is concerned with the importance of the analytical category of gender for the rules structuring the actions of the groups. Gender is perceived as an institution, constructing regulations of access and conduct for its members, shaping the room to maneuver. Do the core elements constituting collective action, namely reputation, trust and reciprocity imply different consequences for men and women? Do the rules structuring group mobilization imply different consequences for men and women in the same given context and regarding the management of the same resource? Where do we observe differences and to which effect? Since action resources are very much determined by the existing construction of gender, the question is how does collective action enlarge or inhibit the choices of men and women. Based on 2005 empirical data, the paper analyzes the tribal community of Kurichyas and the People’s Biodiversity Register with special emphasis on the analytical category of gender concerning the core elements trust, reciprocity and reputation of collective action.